Online Shopping Pattern of Bandung Citizens - Herman S Soegoto (Universitas Komputer Indonesia, 2021)
The objective of this research is to get an insight into the online shopping pattern of Bandung citizens. Research about the online shopping pattern and the impact on businesses ‘with brick and wall’ concept especially in Indonesia is very rare. This research also gives a picture of why a lot of shops with brick and wall concept in Bandung have fewer customers and end up with the closing of the store. The data was obtained from 400 respondents from all districts in Bandung city which were taken by proportional random sampling. Bandung citizens already get accustomed to using the online platform for shopping. The main reasons to shop online are because it is easier, cheaper and faster. The platforms that are frequently used for online shopping are e-commerce and social media. According to this research result, it can be seen there has been a movement on the place to shop for Bandung citizens, where previously most of the citizens shop at bricks and wall retailers but now most of them shift to an online platform. Therefore, entrepreneurs need to reevaluate their businesses by taking into consideration the shift in the shopping pattern of Bandung citizens.